Privacy preserving friend discovery cross domain scheme using re-encryption in mobile social networks - En-tao LUO; Guo-jun WANG; Shu-hong CHEN; Khan-butt PINIAL (Tongxin xuebao)
In order to guarantee the users’ privacy in the process of making friends in the mobile social networks,a new scheme of proxy re-encryption privacy protection in the cross-domain environment was introduced.The scheme employed the cross-domain multi-authority to sharing secret keys,so as to realize the access and shave of the cross-domain users data.And the secret keys of users’ attributes were re-encrypted,based on the technology of the proxy re-encryption and attribute encryption,to achieve the friends matching under the conditions of extending the access policy.Meanwhile,in purpose of enhancing the privacy of users’ data,the technology which contained the separation of users’ privacy ciphertext and secret keys was adopted.Based on that,problems in the existing system such as user data’s inability to be shared cross-cloud,less matching during the process of making friends and users’ inability to make friends when offline had been addressed.Security and experimental analysis show that this scheme can achieve chosen plaintext attack (CPA) security,ensure the privacy of friend discovery,and that is more effective than existing solutions.